The Effect of Organic Fertilizer on Nitrogen Mineralization, Nitrogen Uptake, and Protein Content of Mung Bean (Vigna radiata) in the Sandy Coastal Soil of Parangtritis, Yogyakarta, Indonesia - Maryani, Yekti; Anindita, Rembanang; Lananingrum, Sekar; Arnanto, Driska; Maharani, Artita Devi (Journal of Ecohumanism, 2025)
This research aims to examine the impact of organic fertilizer on nitrogen mineralization in the soil, nitrogen absorption, and the protein content of green bean seeds in sandy coastal areas. The study was carried out in the sandy coastal region of Parangtritis, Kretek, Bantul, Yogyakarta, Indonesia, at an altitude of approximately 10 meters above sea level, with a soil pH ranging from 5.6 to 6.0 and air humidity between 65% and 85%. The soil type is sandy. The experiment was based on a single-factor design, focusing on organic fertilizer, which included seven treatments: no organic fertilizer, cow manure, goat manure, chicken manure, compost, vermicompost, and guanophosphate. Data analysis was conducted using variance analysis at a 5% significance level, while differences between treatments were evaluated using the Duncan Multiple Range Test at the same significance level. The application of organic fertilizer enhances nitrogen mineralization, except in the case of guanophosphate fertilizer. Among the treatments, vermicompost fertilizer resulted in the highest nitrogen mineralization (NNH4) at 43.89 ppm. The application of nitrogen fertilizer also boosts nitrogen absorption and the protein content of green beans. The highest nitrogen absorption was observed with chicken manure at 2.13%, while the highest protein content in green beans was achieved with compost treatment at 22.33%. Additionally, organic fertilizer application contributes to an increase in green bean yield. The highest yields were obtained with compost fertilizer at 1.6 tons per hectare, followed by vermicompost at 1.541 tons per hectare, and guanophosphate at 1.554 tons per hectare.